Ethical examination of deep brain stimulation's 'last resort' status. Issue 12 (13th January 2021) - Stevens, Ian; Gilbert, Frederic
Abstract : Deep brain stimulation (DBS) interventions are novel devices being investigated for the management of severe treatment-resistant psychiatric illnesses. These interventions require the invasive implantation of high-frequency neurostimulatory probes intracranially aiming to provide symptom relief in treatment-resistant disorders including obsessive-compulsive disorder and anorexia nervosa. In the scientific literature, these neurostimulatory interventions are commonly described as reversible and to be used as a last resort option for psychiatric patients. However, the 'last resort' status of these interventions is rarely expanded upon. Contrastingly, usages of DBS devices for neurological symptoms (eg, Parkinson's disease, epilepsy or dystonia) have paved the way for established safety and efficacy standards when used earlier in a disease's timeline. As DBS treatments for these neurological diseases progress to have earlier indications, there is a parallel ethical concern that early implementation may one day become prescribed for psychiatric illnesses. The purpose of this article is to build off contemporary understandings of reversible neurostimulatory interventions to examine and provide clarifications on the 'last resort' status of DBS to better address its ethically charged use in psychiatric neurosurgery. To do this, evaluative differences between DBS treatments will be discussed to demonstrate how patient autonomy would be a paramount guiding principle when one day implementing these devices at various points along a psychiatric disease's timeline. In presenting the clarification of 'last resort' status, the ethical tensions of early DBS interventions will be better understood to assist in providing psychiatric patients with more quality of life years in line with their values.